DIGITAL TWINS IN INDUSTRY: BENEFITS AND TRAPS - Simchenko, Natalia; Tsohla, Svetlana; Molchanov, Igor; Molchanova, Natalya (Revista Inclusiones, 2021)
The article is devoted to the study of the economic and technological advantages of implementing digital doubles in industry. The analysis of digital twins’ market growth trends in high-tech industries is conducted. Based on the analysis of successful practices of implementing digital twins in hightech industries, the advantages of implementing digital twins in industry are presented and justified, based on the basic economic categories: quality, efficiency, costs, and profitability. It is noted that if the stage of predictive Analytics of digital engineering of digital twin design is a technological challenge for companies, it is important for economists to understand the essence of the increase in the effect of using digital twin. From this point of view, the use of digital twins is viewed through the prism of network effects that are generated with the development of digital platforms. The prerequisites for using the Metcalfe law in relation to digital twins are investigated, based on this law, it is possible to analyze the increasing utility of using digital twin technology: devices become "smarter" during operation. The authors point out that the law of increasing utility when using digital twins is associated with such pitfalls for business in the field of security: communication security; device protection; device control; control of network interactions; the closeness of the digital twin system; predictive security Analytics. Along with the considered security pitfalls, economic risks of implementation are highlighted, such as: high cost of implementation solutions, insufficient number of specialists in this field, lack of regulatory acts for the application and use of digital twin strategies. The analysis of the advantages and pitfalls of using digital twins in industry has led to the conclusion that the concept of digital twin is the most important tool for digital transformation of the industry. The success of creating technological superiority of companies in the market is largely determined by the level of technological innovation, the volume of consumer demand, as well as mechanisms for preventing digital piracy.